PO-13 - Production of a functional thrombopoietin by a human ovarian cancer cell line. Issue 140 (April 2016) - Besbes, S.; Helfer, H.; Najah, H.; Fourgeaud, C.; Mirshahi, S.; Soria, J.; Pocard, M.; Ghedira, I.; Mirshahi, M.
Abstract : Introduction: Hemostatic abnormalities are frequently noticed in patients with malignant diseases. These complications include platelets disorders. The role of platelets in cancer extends beyond thrombocytosis and thrombosis, and also platelets promote cancer growth and metastatic dissemination. In the physiology, platelet production is regulated by thrombopoietin, which is mainly secreted by the liver. We, previously, reported that thrombopoietin could be secreted by the ovarian adenocarcinoma cell line, OVCAR-3. Aim: Our main purpose is to analyze the gene expression of thrombopoietin in ovarian cancer cells and to assess its functionality. Materials and Methods: The thrombopoietin gene expression in ascitic cells from patients with ovarian carcinomatosis, as well as, in three cancer cell lines, including OVCAR-3 cells, performed using reverse transcription PCR, real-time PCR and gene sequencing, Normal human ovary and liver tissues are used as controls. The functionality of thrombopoietin on the basis of the viability of a thrombopoietin-dependent cell line (Ba/F3) using a co-culture method. Results: Similarly to liver and ovary tissues, all cancer cells lines express the three TPO-1 (full length TPO), TPO-2 (12bp deletion) and TPO-3 (116pb deletion) variants. By flow cytometry, we show that thrombopoietin production by OVCAR-3 could be increased when cells are stimulated by activated protein C. Lastly, Our results confirm that activated protein C may act, in a paracrine fashion, to boost thrombopoietin production. Conclusions: We report, for the first time, that thrombopoietin secreted by ovarian cancer cells is functional. Hence, thrombopoietin produced by tumor cells may have a direct effect on thrombocytosis/thrombosis occurrence in patients with ovarian cancer.